Characterization of a Digestive α-Amylase in the Midgut of Pieris brassicae L. (Lepidoptera: Pieridae) - Sharifloo, Ali; Zibaee, Arash; Sendi, Jalal J.; Jahroumi, Khalil Talebi (Frontiers in Physiology, 2016)
The current study deals with a digestive α-amylase in the larvae of Pieris brassicae L. through purification, enzymatic characterization, gene expression and in vivo effect of a specific inhibitor, Acarbose. Although α-amylase activity was the highest in the whole gut homogenate of larvae but compartmentalization of amylolytic activity showed an equal activity in posterior midgut (PM) and anterior midgut (AM). A three step purification using ammonium sulfate, Sepharyl G-100 and DEAE-Cellulose Fast flow revealed an enzyme with a specific activity of 5.18 U/mg, recovery of 13.20, purification fold of 19.25 and molecular weight of 88 kDa. The purified α-amylase had the highest activity at optimal pH and temperature of 8 and 35 ºC. Also, the enzyme had Vmax values of 4.64 and 3.02 U/mg protein and Km values of 1.37 and 1.74% using starch and glycogen as substrates, respectively. Different concentrations of acarbose, ethylenediamine tetraacetic acid and ethylene glycol-bis (β-aminoethylether) N, N, N′, N′-tetraacetic acid significantly decreased activity of the purified α-amylase. The 4th instar larvae of P. brassicae were fed on the treated leaves of Raphanus sativus L. with 0.22 mM of Acarbose to find in vivo effects on nutritional indices, α-amylase activity and gene expression. The significant differences were only found in conversion efficiency of digested food, relative growth rate and metabolic cost of control and fed larvae on Acarbose. Also, amylolytic activity significantly decreased in the treated larvae by both biochemical and native-PAGE experiments. Results of RT-PCR revealed a gene with 621 bp length responsible for α-amylase expression that had 75% identity with Papilio xuthus and P. polytes. Finally, qRT-PCR revealed higher expression of α-amylase in control larvae compared to acarbose-fed ones.